Extinção dos contratos de colaboração empresarial: uma abordagem pela teoria dos contratos relacionais - Barros, Simone Rodrigues Alves Rocha de (Universidade de São Paulo, 2024)
The work proposes to investigate the extension of collaboration contracts through traditional tools that rely on the classic contractual model based on exchange and whether these solutions are more suitable for this type of contract. The theory of contracts is to assist in the task of understanding the specifics and the environment of business collaboration contracts and the prospect of terminating the relationship due to the lack of collaboration, based either on default or on the impossibility of the performance itself in the interest of the creditor. In collaboration contracts, collaboration is, by the very definition of these contracts, the main obligation, integral to the core of the contractual object. It is collaboration that is one of the other obligations, allowing the configuration of the common project as a contract. In this type of relationship, the binomial provision and consideration is multifaceted, as are the positions of creditor and debtor. In this context, the study of these collaboration contracts requires a more comprehensive and complex view of the institutes that, originally, were formulated for a tight exchange relationship and for well-defined contractual positions. What we intend to confirm in this research is that the lack of collaboration, in this type of contract, can lead to positive violation or absolute default, which must be determined according to the interest of the creditor which, in corporate contracts, has to do with the economic function, with its own contractual program. Given the difficulty of characterizing a positive breach of the contract or, even more so, absolute default, the investigation also encompasses a broadening of the perspectives of the default itself, to conclude that the performance ultimately serves the interest of the creditor (understood in an amplified position) and can only be read from the economic function of the business. When collaboration between the parties is no longer possible, the specific execution of obligations appears useless and involving.

Limites e desafios do plano de recuperação judicial alternativo de credores - Garcia, Carlos Alberto Junqueira de Andrade (Universidade de São Paulo, 2024)
Esta dissertação tem como objetivo analisar, de forma aprofundada, os principais limites e desafios do plano de recuperação judicial alternativo, cuja legitimidade de apresentação é dos credores e subsidiária à do devedor, instrumento que foi introduzido nas recuperações judiciais apenas recentemente, por meio das alterações promovidas pela Lei no 14.112/2020 na Lei no 11.101/2005 (legislação de insolvência empresarial brasileira). Inicialmente, será explorado o contexto e os motivos que levaram o legislador pátrio a substituir o Decreto-Lei no 7.661/1945, regramento de insolvência que vigeu no Brasil por quase 60 (sessenta anos), por um novo modelo de reestruturação empresarial com natureza e objetivos completamente distintos. Serão feitas, então, breves considerações sobre os processos que sucederam a concordata, a recuperação extrajudicial e a recuperação judicial, destacando o fato de que foi por meio desta última que se recuperou a primazia da negociação, e os credores passaram a ser os principais responsáveis por decidir o destino da empresa em crise. Será feita, então, a análise do plano de recuperação judicial, principal documento e objetivo primário do processo, sua natureza jurídica, conteúdo obrigatório, liberdade de meios de reestruturação, procedimento para a sua aprovação e os limites que devem ser observados. Traçados os seus contornos principais, adentrar-se-á no estudo da sua modalidade alternativa, que pode ser apresentada pelos credores apenas de forma subsidiária e em determinada situações, que serão enfrentadas. Feito isso, serão investigados os limites do plano alternativo de credores que, além dos próprios limites que já incidem sobre o plano do devedor (uma vez que se altera apenas a legitimidade para a sua apresentação), outros específicos que devem igualmente ser observados quando de sua apresentação. Além disso, será demonstrado que, além dos limites legais, existem, ainda, diversos outros desafios de ordem prática que limitam a aplicação dos planos alternativos, especialmente diante das lacunas legais existentes, fazendo com que a sua aplicação prática permaneça ainda restrita, e muito aquém do que foi idealizado pelo legislador. Por fim, considerando que os planos alternativos são um importante instrumento que pode viabilizar a apresentação de propostas melhores pelos devedores (sob pena de ser-lhes imposto um plano de cuja elaboração não participou e cujo conteúdo muito provavelmente não concordará) e tornar mais céleres os processos de recuperação judicial, melhorias na legislação são imprescindíveis, e são feitas sugestões que podem servir como esboço para tanto. This dissertation aims to analyze, in depth, the main limits and challenges to the alternative judicial plan of reorganization, whose presentation legitimacy belongs to the creditors and is subsidiary to the debtor\'s, an instrument that was introduced in judicial reorganizations only recently, through the amendments promoted by Law No. 14,112/2020 in Law No. 11,101/2005 (Brazilian corporate insolvency legislation). Initially, it will be explored the context and reasons that led the Brazilian legislator to replace Decree-Law No. 7,661/1945, an insolvency rule that was in force in Brazil for almost 60 (sixty years), with a new model of business restructuring with a completely different nature and objectives. Brief considerations will then be made on the processes that succeed concordata, extrajudicial reorganization and judicial reorganization, pointing out the fact that it was through the latter that the primacy of negotiation was regained, and creditors became the main responsible for deciding the fate of the company in crisis. An analysis will then be made of the judicial reorganization plan, the main document and primary objective of the reorganization process, its legal nature, mandatory content, freedom of restructuring means, procedure for its approval and the limits that must be observed. With its main contours pointed out, its alternative modality will then be studied, which can be presented by creditors only in a subsidiary way and in certain situations, which will be analyzed. Once this is done, other specific limits to the creditors alternative plan of reorganization will be investigated, in addition to the limits that already affect the debtor\'s plan (since only the legitimacy for its presentation changes). Furthermore, it will be demonstrated that, in addition to legal limits, there are also several other practical challenges to the alternative plans of reorganization that restrict their application, especially given the existing legal gaps, which is yet far lower than what was idealized by legislator. Finally, considering that alternative plans are an important instrument that can force debtors to present better proposals (under penalty of being imposed a plan that they did not elaborate and whose content they most likely will not agree with) and optimize the judicial reorganization processes, improvements in legislation are essential, and suggestions that can serve as an outline for this are made.
Keywords: Alternative plan; Challenges; Creditors plan; Desafios; Judicial reorganization; Judicial reorganization plan; Limites; Limits; Plano alternativo; Plano de credores; Plano de recuperação judicial; Recuperação judicial

Limites à atuação do acionista controlador no regime de recuperação judicial - Dias, Laís Dumitrescu (Universidade de São Paulo, 2024)
Esta Dissertação examina a figura do acionista controlador à luz do contexto da recuperação judicial, com ênfase na legislação brasileira, especialmente a Lei no 11.101/2005, que regula a recuperação de empresas no Brasil. A recuperação judicial é um instrumento jurídico que visa viabilizar a superação de uma crise econômico-financeira da empresa devedora, garantindo a sua continuidade e preservação da função social. Ao mesmo tempo em que o acionista controlador mantém a sua posição de direito após o ajuizamento da recuperação judicial, essa nova situação em que a companhia se encontra poderá alterar de maneira substancial a forma e contornos do exercício do seu poder de controle, seja por força de disposições legais ou pelo surgimento de agentes externos que passarão a ter maior influência nos negócios da companhia, como a coletividade de credores. A fim de analisar as raízes por trás dessas interferências, a Dissertação parte inicialmente de uma investigação da evolução histórica do tratamento legal do acionista controlador no Brasil, tanto do prisma do direito societário quanto do direito falimentar. Em um segundo momento, o trabalho se debruça sobre os impactos específicos da recuperação judicial na atividade do acionista controlador, sempre em comparação entre o que se espera e se observa do comportamento do acionista controlador em situações normal da atividade da companhia. Por fim, serão apresentadas as conclusões extraídas do estudo. This work examines the figure of the controlling shareholder in the context of judicial reorganization, with an emphasis on Brazilian legislation, especially the Brazilian Bankruptcy Act n. 11,101/2005, which regulates the reorganization of companies in Brazil. Judicial reorganization is a legal instrument that aims to make it possible to overcome an economic and financial crisis of the debtor company, guaranteeing its continuity and preserving its social function. While the controlling shareholder retains its position after the filing of the judicial reorganization, this new situation in which the company finds itself can substantially alter the form and contours of the exercise of its power of control, either by virtue of legal provisions or by the emergence of external agents who will have greater influence on the company's business, such as the collectivity of creditors. In order to analyze the roots behind these interferences, the work begins by investigating the historical evolution of the legal treatment of the controlling shareholder in Brazil, both from the perspective of Corporate Law and Bankruptcy Law. Secondly, the work focuses on the specific impacts of judicial reorganization on the activity of the controlling shareholder, always comparing with what is expected and observed of the controlling shareholder's behavior in the company's normal activity. Finally, the conclusions drawn from the study will be presented.
Keywords: Acionista controlador; Controle externo; Controlling shareholder; Creditors; Credores; External control; Joint-stock company; Judicial reorganization; Poder de controle; Power of control; Recuperação judicial; Sociedade anônima

Patentes de invenção, tecnologia e desenvolvimento : exploração local como requisito constitucional e legal das patentes - Vera, Maria Carolina Rezende (Universidade de São Paulo, 2024)
A transferência de tecnologia e a capacitação tecnológica no Brasil são temas relevantes para o debate jurídico nacional, considerando a condição brasileira como país em desenvolvimento. Nesse contexto, a exploração do objeto do direito de patente de invenção em território brasileiro, prevista no art. 68, § 1o, inc. I, da Lei no 9.279/1996, ganha importância. Ao configurar-se como um dos requisitos para o licenciamento compulsório, esse instituto contribui para o alcance das finalidades dos direitos de propriedade intelectual estabelecidas no art. 5o, inc. XXIX, da Constituição Federal de 1988, quais sejam: o interesse social e o desenvolvimento econômico e tecnológico. A partir da matriz constitucional dos Direitos de Propriedade Intelectual, é possível identificar o trígono de finalidades traçadas pelo constituinte originário para esses direitos. Ademais, tais propósitos encontram-se ainda refletidos na Ordem Social brasileira, nos arts. 218 e 219 da Constituição Federal; pois são tarefas do Estado a promoção da inovação e da autonomia tecnológica. A Lei no 9.279/1996 guia-se pelos preceitos estatuídos na Carta Magna, concedendo proteção e privilégio temporário às invenções dotadas de novidade, atividade inventiva e aplicação industrial, nos termos do seu art. 8o. Destaca-se que a exclusividade só é justificada se estiver presente o contributo mínimo. Como é possível extrair dos textos legais, o Estado retira do mercado uma parcela de liberdade de atuação dos agentes econômicos, delegando a gestão privada dos bens a um só deles, com o objetivo de atingir a inovação. Por tais motivos, a legislação prevê uma ameaça aos titulares da patente que não explorem seus direitos dentro do país. A exploração no território brasileiro torna-se uma ferramenta à disposição dos países que não são desenvolvidos para o alcance da inovação. Assim, a presente dissertação propõe-se a relacionar o mecanismo da exploração local aos fins constitucionais e legais das patentes. Por meio de pesquisa qualitativa, aplicada, exploratória e bibliográfica e utilizando os métodos dedutivo e hipotético-dedutivo, este trabalho busca construir uma interpretação sobre a tensão entre acesso de agentes econômicos às tecnologias, exploração das patentes e garantia de exclusividade. O estudo observa que a exploração local é um recurso à disposição dos países em desenvolvimento para que se alcance a inovação e o desenvolvimento econômico e tecnológico. A atuação do Estado no domínio econômico, especialmente no campo dos direitos de propriedade intelectual, foi um recurso utilizado por países atualmente desenvolvidos para alcançar o atual estágio tecnológico em que se encontram. Por tal motivo, é possível que as nações em desenvolvimento utilizem o requisito da exploração obrigatória de patentes em território nacional para difundir avanços sociais, tecnológicos e econômicos. The transfer of technology and technological training within Brazil are relevant topics for the national legal debate, considering the Brazilian condition as a developing country. In this context, the local patent working requirement in Brazilian territory, provided for in art. 68, § 1, inc. I, of Law No. 9,279/1996, gains importance. By being one of the legal requirements for compulsory licensing, this institute contributes to the achievement of the purposes of intellectual property rights established in art. 5th, Inc. XXIX, of the Federal Constitution of 1988, namely: social interest and economic and technological development. From the constitutional matrix of Intellectual Property Rights, it is possible to identify the trigon of purposes traced by the original constituent for these rights. Furthermore, such purposes are still reflected in the Brazilian Social Order, in arts. 218 and 219 of the Federal Constitution; because it is the State\'s task to promote innovation and technological autonomy. Law no 9.279/1996 is guided by the precepts established in the Magna Carta, granting protection and temporary privilege to inventions endowed with novelty, inventive step and industrial application, under the terms of its art. 8th. It should be noted that exclusivity is only justified if the minimum contribution is present. As it is possible to extract from the legal texts, the State withdraws from the market a portion of the freedom of action of economic agents, delegating the private management of assets to one of them, with the objective of achieving innovation. For these reasons, the legislation poses a threat to patent holders who do not exploit their rights within the country. Exploration in Brazilian territory becomes a tool available to countries that are not developed to reach innovation. Thus, the present dissertation proposes to relate the mechanism of local working to the constitutional and legal purposes of patents. Through qualitative, applied, exploratory and bibliographic research and using deductive and hypothetico-deductive methods, this work seeks to build an interpretation of the tension between access of economic agents to technologies, patent local working and guarantee of exclusivity. The study notes that local exploration is a resource available to developing countries to achieve innovation and economic and technological development. The States action in the economic domain, especially in the field of intellectual property rights, was a tool used by currently developed countries to reach the current technological stage in which they find themselves. For this reason, it is possible for developing nations to use the requirement of mandatory exploitation of patents in national territory to disseminate social, technological and economic advances.
Keywords: Compulsory licensing; Desenvolvimento de tecnologia; Desenvolvimento econômico; Economic development; Exploração local; Innovation; Inovação; Licença compulsória; Local working; Patent; Patente de invenção; Technological development

Recuperação extrajudicial : alienação de estabelecimento e inocorrência de sucessão - Filho, Oliveira; De, Paulo Furtado (Universidade de São Paulo, 2024)
Este trabalho tem por objetivo a análise da disciplina da alienação do estabelecimento empresarial na recuperação extrajudicial, especialmente quanto à ocorrência ou não da sucessão do adquirente nas obrigações do alienante. As normas que ensejam a sucessão do adquirente, durante o período de normalidade econômica, buscam proteger os credores, mas contêm desincentivos à celebração do negócio, que tendem a ser ainda maiores num cenário de crise do alienante, diante da perspectiva de que não lhe sobrarão bens bastantes para honrar suas obrigações. Diante disso, a disciplina da alienação do estabelecimento empresarial, na recuperação judicial e na falência, expressamente eliminou a sucessão do adquirente, atraindo maior número de interessados, com a maximização do valor dos ativos e a perspectiva de continuação da atividade, em benefício dos interesses sociais e econômicos que gravitam em torno da empresa, em especial dos empregados, fornecedores, consumidores e o Fisco. Mesmo após o advento da reforma operada pela Lei no 14.112/2020, contudo, não há, na disciplina da recuperação extrajudicial, uma norma clara afirmando a inocorrência de sucessão na alienação de estabelecimento empresarial. Isso explica a preferência pela recuperação judicial em detrimento da extrajudicial, uma solução mais simples, célere e barata para superação da crise do devedor, em benefício dele próprio, dos credores, stakeholders e do funcionamento da máquina judiciária. Daí porque o estudo da disciplina da sucessão na alienação do estabelecimento empresarial ganha especial importância. A depender de como ela for compreendida, o trespasse tanto poderá constituir instrumento de superação da crise e preservação da empresa (ainda que sob outra titularidade), ou ser completamente inviabilizado, em prejuízo dos interesses econômicos e sociais que poderiam ser por ele atendidos. This work focuses on the analysis of the Brazilian legal framework regarding the sale of business in out-of-court restructuring proceedings (known as extrajudicial restructuring), specifically concerning the occurrence or non-occurrence of debt succession from the debtor- seller to the purchaser (successor liability). The rules establishing successor liability for purchasers were drawn up to protect creditors during periods of economic normalcy. However, those rules contain disincentives to the business sale, which tend to be even greater during scenarios of crisis, given the debtors prospects of not having enough assets left to fulfil their obligations. In light of this, Brazilian regulation regarding business sale in judicial restructuring and bankruptcy proceedings explicitly exclude successor liability, attracting a greater number of interested parties, and maximizing asset value and the prospects of continuity for the business activity. All of this in benefit of the social and economic interests that gravitate around the company, especially employees, suppliers, consumers, and the Tax Authority. Nevertheless, even after the reform by Law No. 14,112/2020, there is no clear rule over extrajudicial restructuring stating the non-occurrence of successor liability in a business sale. This explains a preference for judicial over extrajudicial reorganisation, a simpler, faster, and less costly solution for overcoming the debtor\'s crisis, benefiting the debtor himself, the creditors, the stakeholders, and the Judiciarys functioning. Hence, the study of the regulation applied to successor liability in sales of business gains special importance. Depending on how this regulation is understood, the sale can either be a tool for overcoming crisis and preserving the company (even if under different ownership) or it can be made utterly unviable, damaging economic and social interests that could be protected by it.
Keywords: Alienação de estabelecimento; Alienação de unidade produtiva isolada (UPI); Business sale; Extrajudicial restructuring (Out-of-court reorganisation); Recuperação extrajudicial; Successor liability; Sucessão; UPI (Isolated Productive Unit) Sale

A renúncia a direitos fundamentais processuais na arbitragem: o caso particular do direito a requerer a anulação da sentença arbitral na arbitragem internacional - Teles, Joana Ataíde Cordeiro Galvão (Universidade Nova de Lisboa, 2024)
A arbitragem é um meio de resolução de litígios, que se alicerça na autonomia privada e é reconhecida, quer internacionalmente, quer nas constituições estaduais analisadas, como um modo de exercício, alternativo aos tribunais estaduais, do direito fundamental constitucional à tutela jurisdicional efetiva. A questão que se coloca é a de saber se, em primeiro lugar, as partes podem acordar renunciar, validamente, a direitos fundamentais processuais na arbitragem e, podendo, com que requisitos e dentro de que limites, para, em segundo lugar e em particular, aplicar os requisitos e limites referidos à (in)admissibilidade da renúncia ao direito a requerer a anulação da sentença arbitral na arbitragem internacional. Partindo da ponderação do âmbito, conteúdo e regime dos direitos fundamentais em confronto, de um lado, à tutela jurisdicional efetiva, incluindo o direito à arbitragem e outros direitos fundamentais processuais, como o de impugnar a sentença arbitral em determinados casos e, do outro lado, à autonomia privada, que fundamenta a renúncia, e sem prejuízo de a ponderação dever ser feita em cada caso concreto, concluo que a renúncia àqueles direitos é válida, se cumprir determinados requisitos subjetivos e objetivos, que identifico, incluindo os limites e os respetivos critérios para aferir da referida (in)validade. Quanto ao direito a requerer a anulação da sentença arbitral na arbitragem internacional, concluo que, sem prejuízo e com base nas soluções consagradas de jure constituto, a renúncia por acordo das partes é, do ponto de vista constitucional normativo e, de jure constituendo no direito português, válida, desde que se respeitem aqueles requisitos. Em particular, tem de existir um meio de impugnar a sentença arbitral, quando esta viole, de forma grave, direitos fundamentais processuais e/ou interesses de ordem pública de cada Estado, que não estão na disponibilidade das partes, nos casos e termos necessários a garantir o conteúdo essencial do direito fundamental à tutela jurisdicional efetiva. No entanto, há margem do legislador para adotar o regime mais adequado ao propósito referido. Na arbitragem internacional, do ponto de vista normativo-constitucional, podem as partes renunciar, total e/ou parcialmente, à anulação na sede, quando há a possibilidade de controlo último, pelo menos de violações graves de direitos fundamentais processuais e/ou interesses de ordem pública de cada Estado, aquando do reconhecimento e execução da sentença arbitral, sendo esta a solução legal que, na minha opinião, melhor se coaduna com a arbitragem internacional no seu todo. Arbitration is a dispute resolution mechanism rooted in private autonomy and internationally recognised, as well as in the national constitutions analysed, as an alternative means to state courts for exercising the constitutional fundamental right to effective judicial protection. The primary question of this dissertation is whether the parties can validly agree to waive fundamental procedural rights in arbitration, and if so, under what conditions and within what limits. Secondly, I specifically apply these conditions and limits to the (in)admissibility of waiving the right to seek annulment of the arbitral award in international arbitration. By weighing the scope, content and framework of conflicting fundamental rights – the right to effective judicial protection (encompassing the right to arbitration and other fundamental procedural rights, such as the right to challenge the arbitral award in certain cases), against private autonomy (which justifies the waiver) – and, without prejudice to the necessary case-by-case balancing, I conclude that the waiver of these rights is valid, provided that subjective and objective requirements, including the limits and criteria for assessing the (in)validity of the waiver, are met. Regarding the right to request annulment of the arbitral award in international arbitration, I conclude that, without prejudice to and relying on legal solutions established de jure constituto, the waiver by agreement of the parties is valid from a normative constitutional perspective and de jure constituendo under Portuguese Law, provided such subjective and objective requirements are respected. Specifically, there must be a means to challenge the arbitral award when it seriously violates fundamental procedural rights and/or public order interests of each State, which are beyond the parties’ disposal, in certain cases and under certain terms as necessary to protect the core essence of the fundamental right to effective judicial protection. However, the legislator retains discretion to adopt the most appropriate legal framework for this purpose. In the context of international arbitration, from a normative-constitutional perspective, the parties may waive annulment at the seat, in whole and/or in part, provided there is the possibility of ultimate oversight, particularly in cases involving serious violations of fundamental procedural rights and/or public order interests of each State at the stage of recognition and enforcement of the arbitral award. In my opinion, this legal solution is the one that best aligns with the global system of international arbitration.
Keywords: Annulment; Anulação; Arbitragem; Arbitragem Internacional; Arbitration; Autonomia Privada; Direitos Fundamentais Processuais; Fundamental Procedural Rights; International Arbitration; Private Autonomy; Renúncia; Waiver

A responsabilidade das empresas transnacionais na preservação dos direitos indígenas - Alves, Alessandra Vanessa (Universidade Nove de Julho, 2024)
The present study aimed to identify the duties – expressed and implicit – that arise for transnational companies when their economic activities are conducted on indigenous lands or have an impact on them. To this end, identified the most recurrent violations of indigenous peoples' interests regarding the commercial exploitation of their lands or surroundings. Adopting the context of the Krenak people, it was identified that the Krenak, similar to other indigenous peoples, have experienced conflicts on multiple fronts due to large scale projects affecting their territoriality, access to natural resources (with prejudice to their subsistence), and their very way of life and existence. Reflecting on the commitment made to by political entities and their respective branches with the enactment of the Federal Constitution of 1988, the constitutional provisions were interpreted from a historical perspective. It was identified that economic exploitation of indigenous lands -contingent upon legislation - shall, if enacted (because it is not a constitutional duty but a mere possibility), adhere to the criteria previously outlined in the Constitution, including consultation with the peoples concerned, authorization by the National Congress, and the right to participate in the results of the extraction. Furthermore, the principles derived from these criteria include the exceptional nature of exploration, preservation of indigenous wealth - both material and immaterial - and recognition of indigenous thought as a decisive element. It was concluded that these principles entail an extensive list of duties for transnational companies concerning indigenous peoples, which must be implemented with consideration for indigenous worldviews - an underlying assumption for the application of indigenous rights. This list is not static; rather, it should evolve with human rights developments and ensure the ability to address new challenges arising from the relationship between transnational companies and indigenous peoples.
Accepted: 2024-09-11T17:42:54Z
Keywords: CSR; RSE; Responsabilidad Social; Responsabilité sociale de l'entreprise

Os fundamentos da não distribuição do dividendo obrigatório nas sociedades por ações - Valentim, Raphael Matos (Universidade de São Paulo, 2024)
A repartição do lucro entre os sócios é um dos eventos mais relevantes de uma sociedade empresária, tanto é assim que as sociedades por ações possuem uma regra de distribuição obrigatória de dividendos. Entretanto, existem limites juridicamente definidos para que esta distribuição não seja realizada em prejuízo de outros interesses tutelados pela lei. Dividida em duas partes e se valendo da metodologia analítica dedutiva, esta dissertação investiga as hipóteses de não distribuição do dividendo obrigatório aplicáveis para as companhias, identificando as situações que ensejam este não pagamento, bem como analisando criticamente os seus fundamentos e os limites quanto à sua utilização pelas companhias. A primeira parte se divide em dois capítulos, que tratam de conceitos gerais aplicáveis às sociedades, tais como a finalidade lucrativa, o lucro e o direito do acionista ao dividendo, tal qual a sistemática dos dividendos à luz das finanças corporativas. Os quatro capítulos que integram a segunda parte desta dissertação realizam uma avaliação crítica das hipóteses que autorizam o não pagamento do dividendo obrigatório. Durante a análise são realizadas propostas de interpretação do texto legal para solucionar eventuais lacunas existentes na lei com relação a cada uma das hipóteses analisadas, naquilo que possível dentro das limitações da pesquisa. Entre outros resultados, a pesquisa traz contribuições para diferenciar a incompatibilidade da situação financeira da companhia e a crise financeira, confrontando interpretação anterior, que relacionava a incompatibilidade com a iliquidez. A pesquisa também contribui para uma interpretação científica das novas disposições relacionadas à não distribuição do dividendo obrigatório, trazidas pela Lei n. 14.112/20 e pela Lei Complementar n. 182/21, que restringem o pagamento de dividendos. The allocation of profit among shareholders stands as one of the most significant events within a business entity. This is evident in the existence of a mandatory dividend distribution rule in joint-stock companies. Nonetheless, legally defined boundaries exist to prevent such distribution from occurring to the detriment of other interests protected by the law. Split into two parts and employing deductive analytical methodology, this dissertation investigates the scenarios where the mandatory dividend is not distributed in companies, identifying situations that warrant this non-payment and critically analyzing its foundations and limitations concerning its utilization by these companies. The first part comprises two chapters addressing general concepts applicable to corporations, such as profit purpose, earnings, shareholder right to dividends, and the dividend system in light of corporate finance. The second part, composed of four chapters, conducts a critical assessment of the scenarios permitting the non-payment of mandatory dividends. Throughout the analysis, proposals for interpreting the legal text are made to address potential gaps in the law regarding each of the examined scenarios, as far as possible within the research limitations. Among other findings, the research provides insights to distinguish between a companys financial incompatibility and financial crisis, challenging previous interpretations that linked incompatibility solely to illiquidity. Additionally, the study contributes to a scientific interpretation of the new provisions related to the non-distribution of mandatory dividends introduced by Law 14,112/20 and Complementary Law 182/21, which restrict dividend payments.
Keywords: Corporate law; Direito societário; Dividendos; Dividends; Joint-stock company law; Lei das sociedades por ações; Lucros; Non-distribution; Profits; não distribuição

Dano moral por ricochete no Direito Civil: problemas de delimitação e de aplicação sob uma perspectiva histórica, empírica e comparada. - Barreto, Júlia D'Alge Mont'Alverne (Universidade de São Paulo, 2024)
A Tese aborda a reparação dos danos morais por ricochete no Direito Civil brasileiro a partir de perspectiva histórica, empírica e comparada. Objetiva-se contribuir para a definição de critérios da reparação sob dois aspectos: a legitimidade para postulação do ressarcimento e a quantificação do dano. Para tanto, investiga-se a construção da responsabilidade civil por danos morais por ricochete nos ordenamentos jurídicos francês, português e alemão e na jurisprudência de cada país e, depois, examina-se o histórico desta reparação no Direito Civil brasileiro. Em seguida, analisa-se o enfrentamento dos temas centrais pelo Supremo Tribunal Federal e pelo Superior Tribunal de Justiça, em virtude de na jurisprudência verificar-se a tentativa de definição de alguns parâmetros a regerem a reparação dos danos extrapatrimoniais por ricochete. Avalia-se os conceitos e fundamentos legal, doutrinário e jurisprudencial deste tipo de dano e os riscos e vantagens de estabelecer-se, no Brasil, critérios restritivos de indenização, à semelhança do que ocorre nos ordenamentos português e alemão. Por fim, conclui-se que não há critério efetivamente firmado no STJ a respeito da definição da legitimidade para postulação do ressarcimento, pelo que se sugere a adoção de modelo restritivo a partir da utilização da ordem de vocação hereditária estabelecida no artigo 1.829 do Código Civil, à semelhança dos modelos português e alemão, a fim de garantir segurança jurídica e estabilidade conceitual ao tema. A respeito da quantificação do dano, propõe-se não a utilização de tarifação, mas de regulação da quantificação, observando-se os elementos seguintes: (a) possibilidades econômico-financeiras de ofensor e vítima reflexa; (b) grau de culpa do ofensor; (c) extensão do dano reflexo; (d) quantidade de vítimas reflexamente atingidas pelo mesmo evento danoso; e (e) proximidade do vínculo de parentesco entre vítima direta e vítima reflexa.
Keywords: Civil liability; Dano moral por ricochete; Direito Civil; Legitimacy; Legitimidade; Moral damage by ricochet; Private law; Quantification; Quantificação; Responsabilidade civil

Assimetria de poder juridicamente significativa : critérios e impactos na disciplina dos contratos empresariais. - Oliveira, Natália Marques de (Universidade de São Paulo, 2024)
O artigo 421-A do Código Civil justifica o afastamento da presunção de paridade e de simetria dos contratos empresariais mediante a presença de elementos concretos cujo teor, natureza e efeitos não são explicitados. A disposição é, via de regra, relacionada à possibilidade de intervir em contratos marcados pela assimetria de poder de barganha entre os contratantes. Dado que é natural que haja disparidade de poder entre as partes, eventual intervenção para conter ou sancionar os efeitos da liberdade contratual exercida no âmbito de uma relação obrigacional assimétrica apenas é justificada se comprometerem valores jurídicos, razão pela se compreende que nem todo desequilíbrio de poder é e deve ser juridicamente significativo. Portanto, propõe- se o conceito de assimetria de poder juridicamente significativa a partir da interpretação sistemática dos artigos 187, 421, caput e 421-A, caput do Código Civil. O objetivo do trabalho é investigar os critérios para qualificação das práticas contratuais derivadas da assimetria de poder juridicamente significativa, bem como seus impactos no cumprimento dos objetivos da disciplina jurídica aplicável aos contratos empresariais de promover segurança jurídica e confiança aos agentes econômicos. Para alcançar o objetivo proposto, a análise foi realizada a partir de dois recortes, um geral e um específico. Como Recorte de Análise Geral, considerou-se os contratos da cadeia agroalimentar (agronegócio) firmados entre o elo produtor e o segmento a jusante. O Recorte de Análise Específico correspondeu aos contratos firmados entre os citricultores e as indústrias processadoras de suco de laranja. Como resultados, defende-se que é juridicamente significativa a assimetria de poder nos contratos empresariais quando dela resultam práticas contratuais pelas quais o agente com poder superior de barganha transfere, total ou parcialmente, custos e riscos incidentes sobre a operação econômica formalizada pelo contrato à parte com desvantagem negocial, sem que seja justificada, do ponto de vista da estrutura jurídica e/ou econômica do negócio, a ausência de contrapartida para assunção de referidos custos e riscos, comprometendo, ao menos potencialmente, o cumprimento da função socioeconômica imediata e mediata dos contratos empresariais. Ademais, a assimetria de poder juridicamente significativa compromete o cumprimento dos objetivos da disciplina jurídica de conferir segurança jurídica e confiança aos agentes econômicos atuantes em dado mercado, razão pela qual não é efetiva para lidar a contento com a problemática. A partir dos resultados, concluiu-se que são necessárias adaptações a nível de direito material e instrumental para endereçamento dos impactos da assimetria de poder juridicamente significativa, que devem ser objeto de pesquisas futuras. Article 421-A of the Civil Code justifies challenging the presumption of parity and symmetry in business contracts through the presence of concrete elements whose content, nature, and effects are not specified. This provision is generally related to the possibility of intervening in contracts characterized by an asymmetry of bargaining power between the parties. Given that there is naturally a disparity of power between the parties, any intervention to contain or sanction the effects of contractual freedom exercised within an asymmetric obligational relationship is only justified if it compromises legal values. Therefore, it is understood that not every power imbalance is, or should be, legally significant. Hence, the concept of legally significant power asymmetry is proposed based on the systematic interpretation of Articles 187, 421, caput in light of Article 421-A, caput of the Civil Code. The objective of this study is to investigate the criteria for qualifying contractual practices resulting from legally significant power asymmetry and to assess their impacts on the fulfillment of the objectives of the legal framework applicable to business contracts in providing legal certainty and trust to economic agents. To achieve the proposed objective, the analysis was conducted through two scopes, a general one and a specific one. As part of the general analysis, contracts within the agri-food chain (agribusiness) between the producer and the downstream segment were considered. The specific analysis focused on contracts concluded between citrus growers and orange juice processing industries. As a result, it is argued that power asymmetry in business contracts is legally significant when it leads to contractual practices by which the party with superior bargaining power transfers, either entirely or partially, the costs and risks associated with the economic operation formalized by the contract to the disadvantaged party, without the absence of consideration being justified from the perspective of the legal and/or economic structure of the business, thereby compromising the fulfillment of the immediate and mediate socioeconomic function of business contracts. Furthermore, legally significant power asymmetry undermines the achievement of the legal framework\'s objectives to provide legal certainty and trust to economic agents operating in a given market, which is why it is ineffective in adequately addressing the issue. The results led to the conclusion that adjustments are required within both substantive and procedural legal frameworks to tackle the problem effectively, which should be further researched.
Keywords: Assimetria de poder de barganha; Bargaining power asymmertry; Business contracts; Contractual freedom; Contratos empresariais; Função social do contrato; Liberdade contratual; Social function of contracts

Fundamentos jurídicos para a atração de investimentos estrangeiros diretos - Botelho, Rodrigo Jacobina (Universidade de São Paulo, 2024)
A história moderna da humanidade vem demonstrando que jaz míope a visão de que determinado país e sua economia podem viver e sobreviver em estado de isolamento hermético ante a economia globalizada. Não é concebível que determinada sociedade possa se desenvolver sem interação com investidores estrangeiros. Mesmo em países que, por opção ideológica, há certo isolamento, vemos hoje a existência de investimentos estrangeiros, ainda que sejam originados em outros países com o mesmo viés ideológico. Desta forma, os países em desenvolvimento e, em especial para o trabalho que aqui se apresenta, o Brasil têm que compreender as possíveis estruturas jurídicas e econômicas, bem como de políticas públicas que expressam tais estruturas, para poder pretender se credenciar como atrativos destinos de investimentos estrangeiros, seja pela outorga de benefícios (diretos ou indiretos), seja pela segurança ao investidor. No Brasil, entretanto, essa atratividade deve ser sopesada com a preservação de valores fundantes de nossa Constituição, congruentes com o ordenamento jurídico nacional e, ainda, devem ser, depois de efetivado o investimento, acompanhado por um sistema que imponha transparência e solidez ao cumprimento das contrapartidas desejadas: notadamente a geração de emprego e renda e de contribuição para a criação da riqueza nacional. O ponto central do presente trabalho gira em torno dos fundamentos jurídicos para a atração e manutenção, bem como a construção de um possível sistema de aferição da solidez jurídica de políticas de incentivo ao capital estrangeiro.
Keywords: Acompanhamento; Attraction policy; Benefits; Benefícios; Convenience; Conveniência; FDI; Foreign direct investment; Foreign investment; Investimento estrangeiro; Investments; Monitoring; Política de atração

Atribuição de contrapartida em dinheiro nas operações de incorporação e incorporação de ações no direito brasileiro : admissibilidade e limites à luz dos interesses dos acionistas. - Hebling, Julia Corrente (Universidade de São Paulo, 2024)
Esta dissertação parte da seguinte indagação: a contrapartida em dinheiro no âmbito das operações de incorporação e incorporação de ações é admitida no ordenamento jurídico brasileiro? Para responder a essa pergunta, o trabalho examina, em primeiro lugar, de que forma a continuidade das participações societárias insere-se na disciplina dessas operações, constatando que a transposição dos sócios da companhia incorporada (ou cujas ações são incorporadas) para a sociedade incorporadora é tradicionalmente encarada com um traço essencial dessa modalidade de reorganização societária. Nada obstante a essa concepção, o trabalho se dedica a analisar em que medida essas operações são compatíveis com o ordenamento jurídico societário brasileiro, com o propósito de identificar se há fundamentos jurídicos a respaldar a dispensa do princípio da continuidade das participações societárias. Nesse contexto, busca identificar os riscos decorrentes da admissibilidade de operações de incorporação com pagamento em dinheiro sob a perspectiva dos acionistas das companhias envolvidas, avaliando se, diante de tais riscos, as salvaguardas oferecidas pelo ordenamento jurídico societário vigente são suficientes para endereçá-los, assinalando os pontos em que a disciplina jurídica poderia ser aprimorada e a necessidade da imposição de determinados limites à realização dessas operações. This dissertation seeks to answer the following question: is cash consideration in a merger permitted under Brazilian law? In order to answer that question, this study first examines how the participation in the equity of the surviving corporation is traditionally viewed within the legal framework of these transactions, concluding that the passage of the shareholders from the merged company (or whose shares are merged) to the surviving company is seen as an essential feature of mergers. Notwithstanding this conception, this study is dedicated to analyze to what extent such kind of merger is compatible with the Brazilian corporate legal system, with the purpose of identifying whether there are legal grounds to support its admissibility. In this context, the dissertation seeks to identify the risks arising from the admissibility of cash as consideration in mergers from the perspective of the shareholders of the companies involved in such transactions, assessing whether, in light of such risks, the safeguards provided by the current corporate legal system are sufficient to address them, pointing out where the legal framework could be improved and the need to impose certain limits on carrying out these transactions.
Keywords: Admissibilidade de pagamento em dinheiro; Cash as consideration; Cash-out mergers; Exchange ratio; Incorporação; Incorporação de ações; Merger; Merger of shares; Relação de substituição

Trabalhadores em plataforma digital e protagonismo do Direito do Trabalho. Entre intervenção do estado e autorregulação: qual a proteção adequada? - Jesus, Filipe dos Santos Silva (Universidade de São Paulo, 2024)
A presente tese tem por escopo analisar a proteção dos trabalhadores em plataformas digitais. Sob o viés específico, investiga como o Direito do Trabalho pode assumir seu protagonismo na tutela dos motoristas via aplicativos. O trabalho em plataformas digitais já é uma realidade tanto no cotidiano brasileiro quanto nos demais países. São milhares de trabalhadores espalhados por inúmeras atividades via plataformas digitais, havendo crescimento exponencial nessa seara, o que propicia oportunidades, avanços e desafios. Ocorre que, até o momento, ainda não foi definido o standard de proteção aplicáveis a esses trabalhadores, havendo vazio protetivo que gera precariedades, insegurança jurídica e controvérsias judiciais. Por tais razões, a regulação dessa nova forma de trabalho constitui desafio global. Questiona-se: qual é a proteção adequada para os trabalhadores em plataforma digital? Em busca de respostas coerentes, concebe-se que o Direito do Trabalho pode assumir sua eterna juventude, adaptar-se aos novos tempos e se reinventar para proteger também esses novos trabalhadores. A tese defende um regime jurídico moderno, compatível e pacificador, capaz de harmonizar proteção social e segurança jurídica, valor social do trabalho e livre iniciativa, dignidade da pessoa humana e meio ambiente de trabalho saudável. Essa justa medida pode ser encontrada entre a intervenção estatal mínima e a autorregulamentação das partes. Cabendo ao Estado assegurar a dignidade de todos os trabalhadores, no âmbito da livre iniciativa, identifica-se núcleo fundamental de direitos aplicáveis aos trabalhadores em plataformas digitais, levando-se em conta as transformações do mundo de trabalho; respeitada essa normativa mínima do tipo cláusula pétrea ou espaço vital e inflexível, caberá aos próprios atores sociais regular essa peculiar atividade laboral, o que confere maior efetividade, segurança jurídica e adaptação às transformações sociais. The purpose of this doctoral study is to analyze the issue of protecting workers on digital platforms. From a specific perspective, it will investigate how Labor Law can assume its leading role in protecting drivers via apps. In fact, working on digital platforms is already a reality in everyday life in Brazil and in other countries. There are thousands of workers spread across numerous activities via digital platforms, with exponential growth in this area, which provides opportunities, advances and challenges. It turns out that, to date, the protective standard applicable to these workers has not yet been defined, resulting in a protective void that generates precariousness, legal uncertainty and judicial controversies. For these reasons, regulating this new form of work constitutes a global challenge. The question is: what is the adequate protection for platform workers? In search of coherent answers, it is conceived that Labor Law can assume its eternal youth, adapt to new times and reinvent itself to also protect these new workers. It advocates the achievement of a modern, compatible and pacifying legal regime, capable of harmonizing social protection and legal security, the social value of work and free initiative, human dignity and an adequate working environment. This fair measure can be found between minimal state intervention and self- regulation of the parties. As the State is responsible for ensuring the dignity of all workers, within the scope of free enterprise, a fundamental core of rights applicable to workers on digital platforms will be identified, taking into account the transformations in the world of work. Respecting this minimum regulation of the stone clause or vital and inflexible space type, it is believed that social actors themselves will be able to regulate this peculiar work activity, which provides greater effectiveness, legal security and adaptation to social transformations.
Keywords: Appropriate regulation; Digital platform workers; Drivers via apps; Motoristas via aplicativos; Necessary protection; Protagonism of Labor Law; Protagonismo do Direito do Trabalho; Proteção necessária; Regulamentação adequada; Trabalhadores em plataforma digital

A relação entre as normas de direito societário e a lei de recuperação judicial e falência : plano dos credores, aumento de capital e direito de retirada - Lamas, Victor Nader Bujan (Universidade de São Paulo, 2024)
A Lei de Recuperação Judicial e Falência, após a reforma de 2020, permitiu que a maioria dos credores, organizados em assembleia, possam impor medidas à empresa em recuperação judicial e aos seus sócios, nos termos do art. 56, § 4o e seguintes. Embora diversas medidas possam ser adotadas pelo plano dos credores, como é o caso das determinações de aspecto exclusivamente patrimonial e a alteração da administração da empresa em recuperação judicial, algumas providências não podem ser impostas sem que haja a anuência dos sócios, nos termos da legislação societária, como é o caso da fusão, incorporação e transformação. A capitalização dos créditos em recuperação judicial, inclusive com a alteração de controle, é expressamente admitida pela Lei de Recuperação Judicial e Falências, o que enseja, em determinados casos, o exercício do direito de retirada pelos sócios do devedor. O cálculo do recesso para fins de exercício do direito de retirada deve ocorrer mediante um critério exclusivamente patrimonial, sem que seja permitido que os sócios retirantes possam se valer da expectativa de lucratividade futura da sociedade no cálculo do valor da empresa para fins de recesso. O crédito decorrente do direito de retirada possui natureza extraconcursal e não se sujeita aos efeitos da recuperação judicial. Seu pagamento, entretanto, deve ocorrer de maneira compatível com a preservação da empresa, mediante a utilização de um percentual dos resultados futuros, sem que seja possível a venda de ativos da empresa em recuperação para pagamento dos sócios retirantes.
Keywords: Aumento de capital; Capital increase; Classification of credits; Classificação dos créditos; Direito de retirada; Judicial recovery plan; Judicial rehabilitation; Recuperação judicial; Right of withdraw; plano dos credores

Medidas de conservação nos negócios jurídicos condicionados - Lobato, Jose Cristobal Aguirre (Universidade de São Paulo, 2024)
A tese visou analisar o sentido e alcance do artigo 130 do Código Civil. Essa tarefa, no entanto, foi precedida por estudo da estrutura e função da condição dentro do quadro do negócio jurídico, provocando o debate sobre sua utilização, inclusive atípica. Analisou-se dogmaticamente o elemento condição na teoria geral do negócio jurídico, sob uma perspectiva crítica para, depois, estudar a fase de pendência e as obrigações dela decorrentes para os figurantes e as possibilidades em tema de atos conservativos, nessa etapa tão característica do negócio condicionado, oferecendo novos enfoques para o assunto. Isso se fez de modo propositivo, aproveitando ainda para ponderar sobre as implicações da cláusula geral de boa-fé nessa matéria. Por fim, apresenta rol de considerações de caráter operativo, tentando estabelecer a conexão entre os atos conservativos a que alude a lei civil, com as devidas repercussões processuais. The thesis aimed to analyze the meaning and scope of article 130 of the Civil Code. This task, however, was preceded by a study of the structure and function of the condition within the framework of the legal business, bringing up the debate on its use, including atypical use. It was carried out a dogmatic analysis of the condition element in the general theory of the legal business, from a critical perspective, in order to study the pendency phase and the obligations it entails for the parties and the possibilities in terms of conservative acts at this stage, which is so characteristic of the conditioned transaction, offering new approaches to the subject. This was done purposefully, taking the opportunity to consider the implications of the general clause of good faith in this matter. The final considerations were presented in an operative view, trying to establish the connection between the conservative acts referred to in civil law, with the appropriate procedural repercussions.
Keywords: Condition; Conditional Legal Transactions; Condição; Direito Civil; Fato Jurídico; Legal Fact; Negócios Jurídicos Condicionados; Private Law

Dano informacional no mercado de valores mobiliários - Ronco, Felipe dos Santos (Universidade de São Paulo, 2024)
Ao acessar o mercado de valores mobiliários, atribui-se às companhias emissoras um dever de sempre informar, a tempo e modo, seus respectivos investidores, sejam eles atuais ou futuros, de modo a assegurar que todas as informações por elas divulgadas ao mercado, de forma voluntária ou obrigatória, sejam fidedignas. A despeito do efeito que possa produzir na decisão individual do investidor, a informação sempre terá um impacto na própria cotação dos valores mobiliários, uma vez que considerado seu ambiente de negociação (i.e., o sistema de pregão) e as forças de oferta e demanda do mercado. O efeito da informação na expectativa individual do investidor será irrelevante para a formação dos preços dos valores mobiliários, devendo o efeito do ilícito informacional ser apurado a partir de todo o conjunto de operações realizadas em bolsa. O dano informacional deve, assim, ser compreendido a partir da violação do interesse juridicamente tutelado do investidor nas informações prestadas pela companhia emissora, tendo em vista os efeitos que essas informações são capazes de produzir diretamente na cotação dos valores mobiliários. When accessing the securities market, issuers have the duty to inform, in a timely manner, their investors, whether current or future, in order to ensure that all information disclosed to the market, whether voluntarily or obligatory, is reliable. Regardless of the effect it may have on the investor\'s decision, the information will always have an impact on the price of the securities itself, once considered their trading environment (i.e., the trading system) and the forces of supply and demand of the market. The effect of the information on the investor\'s individual expectations will be irrelevant to the formation of securities prices, since the effect of unlawful wrongdoing must be determined based on the entire set of operations carried out on the stock exchange. Informational damage must, therefore, be understood as the violation of the investor\'s legally protected interest in information provided by the issuer, considering the effects that the information produces directly on the price of securities.
Keywords: Dano informacional; Dever de informação; Duty to inform; Informational damages; Investidor; Investor; Mercado secundário; Secondary market

A companhia engajada : disciplina dos atos societários de orientação social - Galizzi, Gustavo Oliva (Universidade de São Paulo, 2024)
Os acadêmicos divergem desde sempre a respeito do objetivo da companhia: atender ao interesse dos acionistas e buscar a maximização dos resultados ou, alternativa ou sucessivamente, atender ao interesse de outras partes interessadas? Porém, as linhas entre uma e outra correntes não são mais nítidas como antes. Com o crescente interesse nas chamadas métricas de ESG a sigla para Environmental, Social and Governance, modelos híbridos de governança têm sido pensados a partir da combinação de lucro e propósito. Nesse sentido parece evidente a consolidação de uma tendência no direito societário que, por falta de um termo melhor, possa ser qualificada como preponderantemente social. Sem prejuízo dessa evidência, o objetivo do trabalho não é o de defender uma ou outra corrente sobre a função da companhia. Num olhar pretensamente original, o estudo propõe outro enfoque: traçar a disciplina legal dos atos societários de orientação social, como materialização do interesse que os precede. Academics have always disagreed about the company\'s objective: to serve the interests of shareholders and seek to maximize results or, alternatively or successively, to serve the interests of stakeholders as other interested parties? However, the lines between one theory and another are no longer as clear as before. With the growing interest in the so-called ESG metrics the acronym for Environmental, Social and Governance, hybrid governance models are being designed based on the combination of profit and purpose. The consolidation of a trend in corporate law that, for lack of a better term, can be qualified as predominantly social is now clear. Notwithstanding the before, the objective of the study is not to defend one or another theory of the corporate objective. In an allegedly original perspective, the study proposes another approach: tracing the legal discipline of socially oriented corporate acts, as the externalization of the interest that precedes them.
Keywords: Atos societários de orientação social; Corporate objective; Corporate purpose; ESG; Interesse social; Propósito social; Socially oriented corporate acts

Internalização do interesse público na governança corporativa das empresas estatais - Nakasone, William Joji (Universidade de São Paulo, 2024)
A tese aborda as empresas estatais no contexto da Constituição Federal de 1988, destacando seu papel como instrumentos de ação do Estado na busca pela concretização dos objetivos constitucionais. O texto explora as características das empresas estatais, ressaltando sua submissão aos princípios da Administração Pública, bem como aos controles inerentes a essa esfera, como a tutela administrativa, o controle dos tribunais de contas e o controle jurisdicional. Destaca-se a importância do preenchimento do conteúdo do interesse público como guia para o exercício do poder de controle acionário e para a atuação dos órgãos sociais das empresas estatais. Nessa tarefa, propugna-se pela utilização de fontes legítimas de expressão do interesse público que, preferencialmente, e em alguma medida, passaram por processos de inclusão participativa daqueles afetos ao interesse público, seja direta ou indiretamente. Argumenta-se pela maior efetividade de políticas públicas que contam com essa natureza, baseados em experiência desenvolvimentista e na teoria da nova governança pública. Defende a organização e formalização do exercício do poder de controle societário, apoiando a criação de um colegiado para concentrar essa atividade, de modo a garantir formalização das orientações, devida consideração ao conteúdo do interesse público, e sopesamento da matéria vis-à-vis os demais interesses que o acionista controlador deve lealmente respeitar e atender. A tese destaca a necessidade de acomodar o interesse público nos órgãos da administração das empresas estatais, defendendo a nomeação de representantes dos titulares desse interesse no conselho de administração, assim como o estabelecimento de órgão interno com competência técnica de pesquisa, interação com a comunidade e elaboração de políticas relacionadas ao interesse público tutelado. Além disso, expõe sobre o conteúdo do interesse social da empresa estatal e aborda questões relacionadas aos deveres fiduciários do acionista controlador e dos administradores, enfatizando as peculiaridades resultantes da centralidade do interesse público no interesse social. Destaca os mecanismos de organização do exercício do poder de controle, para prevenção e controle de abusos de poder e situações de conflito de interesses. Destaca a contribuição dos mecanismos de tutela do interesse público no interior dos órgãos sociais da empresa estatal para o cumprimento dos deveres de diligência e lealdade dos administradores, prevenindo desvios de poder e assegurando a comutatividade nas operações da empresa estatal com partes relacionadas. The thesis addresses the state-owned enterprises within the context of the Brazilian Federal Constitution of 1988, highlighting their role as instruments of state action in pursuit of constitutional objectives. The text explores the characteristics of state-owned enterprises, emphasizing their adherence to the principles of Public Administration, as well as the controls inherent in this sphere, such as administrative supervision, oversight by audit courts, and judicial control. The importance of defining the content of the public interest as a guide for exercising shareholder control and the functioning of the corporate bodies of state-owned enterprises is emphasized. In this endeavor, the thesis advocates the use of legitimate sources for expressing the public interest that, preferably, to some extent, have undergone participatory inclusion processes of those affected by the public interest, either directly or indirectly. The argument is made for the greater effectiveness of public policies with this nature, based on developmentalist experiences and the theory of new public governance. The thesis advocates for the organization and formalization of the exercise of shareholder control, supporting the creation of a board to centralize this activity, ensuring formalization of orientations, due consideration of the content of the public interest, and weighing the matter against other interests that the controlling shareholder must respect and uphold within its duty of loyalty. The thesis highlights the need to accommodate the public interest in the administration of state- owned enterprises, advocating for the appointment of representatives of those holding this interest on the board of directors, as well as the establishment of an internal body with technical role for research, interaction with the community, and the formulation of policies related to the protected public interest. Additionally, it discusses the content of the company interest of the state-owned enterprise and addresses issues related to the fiduciary duties of the controlling shareholder and administrators, emphasizing the particularities resulting from the centrality of the public interest in the company interest. It emphasizes the mechanisms for organizing the exercise of share control power, for the prevention and control of abuses of power and conflicts of interest. The thesis highlights the contribution of mechanisms to protect the public interest within the corporate bodies of the state-owned enterprise to fulfill the duties of diligence and loyalty of administrators, preventing abuses of power and ensuring arms length basis in the operations of the state-owned enterprise with related parties.
Keywords: Company interest; Corporate governance; Empresas estatais; Empresas públicas; Governança corporativa; Interesse público; Interesse social; Mixed economy companies; Public companies; Public interest; Sociedades de economia mista; State-owned enterprises

O propósito específico nas sociedades empresariais - Andrade, Alexandre Soares (Universidade de São Paulo, 2024)
As sociedades de propósito específico (SPEs) não configuram um tipo societário próprio, mas sim mera categoria eficacial autônoma. A investigação histórica do instituto evidencia raízes desde os tempos romanos, tendo reverberado, ainda, nos arranjos típicos do período medieval e nas codificações oitocentistas, revelando sua essência como uma necessidade comercial da vida prática de separar patrimônios em função de um propósito específico, com projeções internas e externas que foram moldadas ao longo do tempo para viabilizar a consecução de empreendimentos de alto risco e promover o desenvolvimento econômico. No Brasil, está presente desde o Código Comercial de 1850, tendo sido adotada por diversas legislações esparsas ao longo dos últimos séculos para as mais diversas funções, servindo como mola propulsora ao desenvolvimento econômico. Como categoria eficacial autônoma que é, goza de flexibilidade para ser aplicada a qualquer tipo societário, modulando os efeitos típicos que lhes são assegurados aos seus ordenamentos societário, patrimonial e da atividade em função do propósito específico almejado. Não por outro motivo, seguindo o que nos parece ser a melhor técnica, o legislador tratou sua previsão normativa expressa no dispositivo de que trata do objeto social, restringindo-o em função de um propósito específico. Aos aplicadores do direito, diante do desenvolvimento histórico do instituto de seus efeitos, cabe saber distingui-los e aplicá-los, de modo a assegurar a efetividade da categoria em nosso ordenamento jurídico e o desempenho de sua função socioeconômica moldada ao longo de tantos anos.
Keywords: Activity structure; Asset structure; Autonomous efficacy category; Categoria eficacial autônoma; Corporate structure; Modulation of effects; Modulação de efeitos; Ordenamento da atividade; Ordenamento patrimonial; Ordenamento societário; Propósito específico; Sociedade de Propósito Específico (SPE); Special Purpose Entity (SPE); Specific purpose

A representatividade dos credores na recuperação judicial : uma análise da organização dos credores em classes na Lei 11.101/05 - Piva, Fernanda Neves (Universidade de São Paulo, 2024)
Esta Tese de Doutorado apresenta uma análise da legitimidade das deliberações em assembleias-gerais de credores em processos de recuperação judicial no Brasil, sob a ótica das normas estabelecidas pela Lei 11.101/05 e suas alterações pela Lei 14.112/20. O estudo é estruturado em seis capítulos. O primeiro capítulo corresponde à introdução. O segundo capítulo trata do papel dos credores na recuperação judicial, examinando os objetivos da recuperação judicial enquanto um processo de negociação estruturada. O terceiro capítulo aborda a estrutura rígida de divisão dos credores em classes, evidenciando problemas decorrentes da reunião de credores com interesses heterogêneos na mesma classe. Também no terceiro capítulo, a pesquisa analisa a criação de subclasses nas recuperações judiciais, com a possibilidade de tratamento diferenciado de credores, com vistas a avaliar se tais práticas mitigam o problema da legitimidade das deliberações quanto ao plano de recuperação judicial e atendem aos objetivos de uma recuperação judicial eficiente. O quarto capítulo analisa como a organização dos credores em classes ocorre em sistemas de outros países, buscando alternativas e soluções para os desafios identificados no sistema brasileiro. O quinto capítulo propõe soluções e medidas mitigatórias aos problemas identificados no estudo, visando a otimizar o processo deliberativo e garantir uma representação mais efetiva dos interesses dos credores, incluindo possíveis alterações legislativas. No último e sexto capítulo, serão sintetizadas as conclusões que podem ser extraídas do trabalho como um todo. This Doctoral Thesis presents an analysis of the legitimacy of deliberations in general meeting of creditors in judicial reorganization proceedings in Brazil, under the perspective of the norms of the Law 11.101/05 and its amendments by Law 14.112/20. The study is structured in six chapters. The first chapter corresponds to the introduction. The second chapter deals with the role of creditors in judicial reorganization proceedings, examining the objectives of a judicial reorganization proceedings as a proceeding of structured negotiation. The third chapter addresses the rigid structure of division of creditors into classes, highlighting problems arising from the gathering of creditors with heterogeneous interests in the same class. Also in the third chapter, the research analyzes the creation of subclasses in judicial reorganization proceedings, with the possibility of different treatment to creditors, to assess whether such practices mitigate the problem of the legitimacy of deliberations regarding the judicial reorganization plan and meet the objectives of an efficient judicial reorganization proceedings. The fourth chapter examines how the organization of creditors into classes occurs in systems of other countries, seeking alternatives and solutions to the challenges identified in the Brazilian system. The fifth chapter proposes solutions and mitigating measures to the problems identified in the study, aiming to optimize the deliberative process and ensure a more effective representation of the interests of creditors, including possible legislative changes. In the last and sixth chapter, the conclusions that can be drawn from the work will be synthesized.
Keywords: Assembleia Geral de Credores; Bankruptcy; Classes de credores; Classes of Creditors; Creditors; Credores; General Meeting of Creditors; Judicial Reorganization; Lei de Recuperação Judicial e Falências; Recuperação judicial

A mobilização de acionistas nas companhias abertas : interessados, finalidades e instrumentos - Fritz, Maximilian Kiderlen (Universidade de São Paulo, 2024)
Este trabalho tem por objetivo analisar a mobilização de acionistas para as assembleias gerais de acionistas das companhias abertas. Em caráter preliminar, são traçadas algumas premissas sobre o direito de voto, o princípio majoritário, o absenteísmo dos acionistas nas assembleias gerais e algumas considerações sobre dispersão acionária e certos aspectos das minorias societárias. Em seguida, dedicam-se algumas seções aos interessados na mobilização dos acionistas, que podem ser múltiplos e incluem o próprio controlador ou o bloco de referência da companhia, a administração da companhia, os acionistas minoritários na manifestação mais comum da mobilização , e outros interessados que podem consistir em empregados, credores ou membros da sociedade em geral. Feitas essas considerações, a dissertação trata das finalidades jurídicas mais comuns buscadas com a mobilização dos acionistas como, exemplificativamente, a própria convocação das assembleias gerais, tomada das contas, deliberação sobre as demonstrações financeiras, destinação de resultados, eleição de membros do conselho de administração, instalação e eleição dos membros do conselho fiscal, a responsabilização do controlador ou dos administradores e certos eventos que diluem a participação acionária dos acionistas. Por fim, a dissertação trata de alguns instrumentos disponíveis no ordenamento jurídico que podem ser utilizados para a mobilização dos acionistas, como as assembleias digitais ou híbridas, o boletim de voto a distância, a representação de acionistas, o pedido público de procuração, o pedido de lista de acionistas, as mídias sociais, os voting advisors, o empréstimo de ações e o usufruto de ações. This work aims to analyze the mobilization of shareholders for general shareholders\' meetings of publicly traded companies. Preliminarily, some assumptions and premises are outlined regarding the right to vote, the majority principle, shareholder absenteeism at general meetings, and considerations on share dispersion and certain aspects of minority interests. Subsequently, several sections are dedicated to the stakeholders involved in mobilizing shareholders, which may include the controlling shareholder or the company\'s reference block, the company\'s management, minority shareholders in the most common form of mobilization and other interested parties that may consist of employees, creditors, or members of society in general. With these considerations in mind, the dissertation addresses the most common legal purposes sought with the mobilization of shareholders, such as, for example, convening general meetings, approval of financial statements, determination of results allocation, election of members of the board of directors, installation and election of members of the fiscal council, holding the controller or administrators accountable, and certain events that dilute shareholders\' equity participation. Finally, the dissertation discusses some legal instruments available that can be used for shareholder mobilization, such as digital or hybrid assemblies, distance voting bulletins, shareholder representation, public proxy solicitation, shareholder list request, social media, voting advisors, stock lending, and share usufruct.
Keywords: Acionistas minoritários; Assembleias gerais; Companhias abertas; Corporate governance; Corporate law; Direito societário; General meetings; Governança corporativa; Minority shareholders; Mobilização de acionistas; Publicly traded companies; Shareholder mobilization

Anotações sobre a agregação de credores em classes na recuperação judicial de empresas. - Martins, Aline de Toledo (Universidade de São Paulo, 2024)
Este trabalho tem por objetivo a análise da agregação dos credores em classes no âmbito da recuperação judicial, de acordo com a Lei n. 11.101/2005, e os impactos procedimentais e principiológicos neles englobados, tais como: a aprovação do plano de recuperação judicial, a agregação dos credores em classes, o sistema de votação e os princípios da par condicio creditorum e da preservação da empresa, extraindo desta análise lacunas e mecanismos criados que possam ter como consequência o desvirtuamento do fim almejado, sendo ao final apresentadas premissas e hipóteses de limitação e aplicação prática da agregação para evitar práticas abusivas. Dessa forma, são apresentadas breves noções introdutórias e fundamentais sobre a recuperação judicial acompanhada pela apresentação dos conceitos básicos referentes ao plano de recuperação judicial e a divisão dos credores em classes, demonstrando as origens, objetivos e expectativas do estabelecimento das classes na forma apresentada na Lei n. 11.101/2005. Ainda, são objetos específicos de estudo, a análise de como a divisão de classes de credores interfere na votação do plano de recuperação judicial e como tem sido tratada a possibilidade da criação de subclasses como é o caso do credor estratégico - e os efeitos diretos e indiretos ao procedimento e credores envolvidos. Em seguida, tem-se como objetivo verificar, no âmbito legal, as disposições sobre o tema a exemplo do artigo 41 da Lei n. 11.101/2005 -, as consequências e os impasses verificados ao longo dos anos de vigência de referida lei que demandam atenção e alterações para que o tratamento aos credores no âmbito da recuperação ocorra de forma mais justa e adequada aos interesses de todos os envolvidos. Assim, serão expostas soluções alternativas para a melhor condução do procedimento da recuperação judicial em relação às classes de credores e subdivisões em busca de garantir e preservar o objetivo da recuperação judicial, sempre considerando os fatores econômicos, políticos e sociais que influenciam para a análise da viabilidade econômica da empresa e que estão sempre em constante modificação. This work aims to analyze the aggregation of creditors into classes within the scope of judicial reorganization in accordance with Law No. 11.101/2005, as well as the procedural and principled impacts involved, such as the approval of the judicial reorganization plan, the aggregation of creditors into classes, the voting system, and the principles of par condicio creditorum and preservation of the company. It aims to identify gaps and mechanisms that may lead to the distortion of the intended purpose and presents premises and hypotheses for limiting and practically implementing the topic to avoid abusive practices. Thus, this work presents brief introductory and fundamental notions about judicial reorganization by the presentation of basic concepts related to the judicial reorganization plan and the division of creditors into classes, demonstrating the origins, objectives, and expectations of the establishment of classes as presented in Law No. 11.101/2005. Furthermore, specific study objectives include analyzing how the division of classes of creditors affects the voting on the judicial reorganization plan and how the possibility of creating subclasses - such as strategic creditors - has been addressed and its direct and indirect effects on the procedure and involved creditors. Next, this work verifies the legal provisions on the topic - such as Article 41 of Law No. 11.101/2005 as well as the consequences and impasses observed throughout the years of the law\'s existence that demands attention and changes to ensure that treatment of creditors in the context of reorganization occurs in a more just and appropriate manner for all parties involved. Thereby, alternative solutions will be presented for better management of the judicial reorganization procedure regarding creditor classes and subdivisions to ensure and preserve the objective of judicial reorganization, always considering the economic, political, and social factors that influence the analysis of the company\'s economic viability, which are constantly changing.
Keywords: Classification of claims; Classificação de Créditos; Judicial Reorganization; Par condicio creditorum; Recuperação Judicial

Os deveres legais dos administradores de sociedades anônimas em crise - Lunardi Filho, Ferdinando Cesar (Universidade de São Paulo, 2024)
Este trabalho apresenta a tese de que, embora as normas constantes dos arts. 153 e seguintes da Lei no 6.404/76 continuem aplicáveis e o objeto dos deveres legais dos administradores de sociedades anônimas permaneça inalterado mesmo após a instauração de um cenário de crise econômico-financeira na companhia, em grande medida regrado pela Lei no 11.101/05, a instalação da referida crise causa uma modificação no conteúdo desses deveres. Para tanto, o trabalho adota como ponto de partida a jurisprudência e a literatura especializada norte-americanas, apresentando criticamente os casos mais recentes e relevantes julgados pelas Cortes de Delaware, bem como uma sistematização da literatura especializada pertinente. A análise crítica dos casos da jurisprudência norte-americana permite a compreensão da transição de um entendimento baseado na trust fund doctrine, segundo o qual, após a instauração da insolvência, mediante a aplicação da insolvency exception, haveria um shift por meio do qual os credores passariam a ser os destinatários dos deveres fiduciários dos administradores, para o entendimento mais recente de que o destinatário dos deveres fiduciários é apenas a companhia, ainda que devam ser levados em consideração pelos administradores os demais interesses que compõem o interesse social, tais como os interesses de credores, trabalhadores, consumidores. Em seguida, considerando que o conceito de crise econômico-financeira tem contornos incertos, o trabalho busca identificar instrumentos indicadores da instalação da crise. Para tanto, o trabalho não apenas revisita os conceitos clássicos de insolvência e insolvabilidade, mas também propõe novos enquadramento e sistematização, visando ao apontamento de elementos objetivos que, considerados em conjunto, permitam identificar com maior nitidez os contornos do estado de crise econômico-financeira. Posteriormente, o trabalho trata do tema central desta tese, começando pela lógica, os limites e a dinâmica da administração de sociedades anônimas em crise, especialmente diante da colidência de interesses de acionistas e de credores e da intensificação desses conflitos depois de instaurado o cenário de crise, passando pela contínua aplicabilidade da Lei no 6.404/76 e pelas razões que levam à alteração do conteúdo dos deveres legais dos administradores de sociedades anônimas em crise. A seguir, o trabalho demonstra que o ângulo mais adequado à análise dos deveres legais dos administradores de sociedades anônimas em crise no Brasil não é o da alteração do objeto dos deveres, nem o da alteração dos seus destinatários, tampouco o da alteração dos titulares de interesses contingentes na companhia, mas sim o da modificação do conteúdo dos referidos deveres. O trabalho adota, ainda, uma lente pragmática, buscando compreender a dimensão em que o conteúdo dos deveres é modificado após a instauração da crise, considerando uma lista exemplificativa das hipóteses mais relevantes, do ponto de vista prático e acadêmico, em que tais deveres entram em discussão: (i) dever de conhecer a situação econômico-financeira da companhia; (ii) deveres informacionais; (iii) dever de avaliar a adoção de medidas de reestruturação e de evitar o agravamento da crise; (iv) deveres relacionados à alienação e oneração de ativos; e (v) deveres relacionados à contratação de novos financiamentos. Por fim, o trabalho apresenta e discute a apuração da responsabilidade e outras possíveis consequências decorrentes do eventual descumprimento dos deveres legais dos administradores das sociedades anônimas em crise. This study presents the thesis that, although the norms set forth in articles 153 and following of Law No. 6,404/76 remain applicable and the object of the legal duties of administrators of public companies remains unchanged after the onset of a scenario of economic and financial crisis in the company, largely regulated by Law No. 11,101/05, financial distress causes a modification in the content of these duties. To this end, the study takes as its starting point the north American precedents and literature, critically presenting the most recent and relevant cases judged by the Delaware Courts, as well as a systematization of the relevant literature. The critical analysis of cases from north American jurisprudence allows the comprehension of the transition from an understanding based on the trust fund doctrine, according to which, after the onset of insolvency, through the application of the insolvency exception, there would be a shift whereby creditors would become the recipients of the fiduciary duties of directors, to the more recent understanding that the recipient of fiduciary duties is only the company, although directors should take into account other interests that compose company`s interest, such as the interests of creditors, workers, consumers. Next, the study investigates the concept of economic and financial distress. Considering that this concept has uncertain contours, the study seeks to identify indicative instruments of the installation of the economic and financial crisis. To do so, the study not only revisits classical themes, such as the concepts of insolvency and insolvability but also proposes new frameworks and systematization, aiming to highlight objective elements that, considered together, allow a clearer identification of the state of economic and financial crisis. Subsequently, the study addresses the central theme of this thesis, beginning with the logic, limits, and dynamics of the administration of companies in financial distress, especially in the face of the collision of interests between shareholders and creditors and the intensification of these conflicts after the onset of the crisis scenario, going through the continuous applicability of Law No. 6,404/76 and the reasons that lead to the alteration of the content of the legal duties of directors of companies in financial distress. Afterwards, the work demonstrates that the most appropriate approach to analyzing the legal duties of administrators of companies in crisis in Brazil is not that of changing the duties\' scope, nor altering their recipients, nor changing the holders of contingent interests in the company. Instead, the work advocates for examining the modifying content of these duties. The work also adopts a pragmatic lens, seeking to understand the extent to which the content of these duties is altered after the onset of the crisis, considering an illustrative list of the most relevant hypotheses, from practical and academic points of view, in which such duties come into discussion, namely: (i) duty to know the economic and financial situation of the company; (ii) informational duties; (iii) duty to assess the adoption of restructuring measures and to avoid the worsening of the crisis; (iv) duties related to the alienation and encumbrance of assets; and (v) duties related to the contracting of new financing. Finally, the study presents and critically discusses aspects related to the determination of responsibility and other possible consequences arising from the eventual non-compliance with the legal duties of managers and directors of companies in the brink of insolvency.
Keywords: Administradores; Corporation; Deveres fiduciários; Directors; Direito da empresa em crise; Fiduciary duties; Insolvency law; Judicial restructuring; Managers; Recuperação judicial; Sociedade anônima

Os Dispute Boards e sua função social: conflitos empresariais em contratos complexos - Possato, Karim Regina Nascimento (Universidade Nove de Julho, 2024)
El estudio de los Dispute Boards (DB) y su función social reflejada a través de la prevención y resolución de conflictos empresariales en contratos complejos es el tema central de este estudio. El problema de investigación planteado, en este contexto, es si los Dispute Boards son institutos capaces de desempeñar una función social basada en la prevención y resolución de conflictos en contratos mercantiles complejos. Así, el tema se desarrolla con base en el método dialéctico de la producción científica, apoyado en investigaciones bibliográficas y documentales, además de investigaciones de campo, con encuestas cuantitativas y cualitativas sobre el uso de los DBs. Para ello, el estudio busca contextualizar los conceptos que involucran al mercado, la empresa y la función social como factores que permean contratos comerciales complejos, caracterizados por incertidumbres y riesgos relacionados con la ejecución contractual que deben ser gestionados a través de la implementación de una gobernanza guiada. por principios que implementen la eficiencia de la relación comercial. La referencia a estándares internos en el ámbito de la administración pública también se utiliza para guiar el estudio, que también se abarca en la aplicación del gobierno corporativo, identificando los DBs como vectores para implementar contratos complejos y, en consecuencia, promover y entregar valor sostenible a las empresas. y otras partes interesadas, concluyendo que son mecanismos relevantes para promover la función social, prevenir y resolver conflictos, especialmente en contratos complejos. De la misma manera, se identifica la necesidad de potenciar el instituto DB, atribuyendo personalidad jurídica, además de la contractual, a sus decisiones, con el fin de potenciar su propia función social basada en la seguridad jurídica de los dictámenes deliberantes vinculantes emitidos, presentando, al final, una propuesta de proyecto de ley con el objetivo de iniciar el proceso legislativo para implementar esta realidad jurídica, siguiendo el ejemplo del instituto de arbitraje.
Keywords: Complex business contract; Contractual governance; Contrato comercial complejo; Contrato empresarial complexo; Dispute Board; Função social; Gobernanza contractual; Governança contratual; Papel social; Social function

Interesse público em atos de concentração : a defesa da segurança econômica nacional - Tokuzumi, Pedro Yukimitsu Ribeiro (Universidade de São Paulo, 2024)
A narrativa da globalização é ambígua, visto que, em âmbito internacional, o discurso é de liberalização dos mercados para que as empresas mais eficientes e inovadoras prosperem; contudo, no plano doméstico, os Estados Nacionais procuram controlar minuciosamente a entrada de capital estrangeiro em seu território. Em especial, esse controle recai sobre a aquisição de empresas nacionais, já que essas operações econômicas podem transferir o controle de: (i) mercados nacionais (ii) tecnologia crítica e know-how; (iii) infraestrutura estratégica; e (iv) informações e dados sensíveis. Trata-se de elementos que, individualmente ou em conjunto, influenciam a soberania de um país. Por força do discurso liberalizante da globalização, é comumente propagado que a análise antitruste no controle de estruturas deve ser neutra e focada no trade-off entre eficiência e os efeitos deletérios unilaterais, coordenados e de fechamento de mercado que eventualmente possam existir em um ato de concentração. Dessa forma, a presente tese de doutorado investiga fenômenos jurídicos que fogem do consenso do direito concorrencial ortodoxo, a saber: (i) a incidência de inúmeros interesses para bloquear investimento estrangeiros indesejáveis em empresas e ativos nacionais; (iii) os efeitos dos subsídios estatais em empresas privadas (campeões nacionais) e públicas (empresas estatais) para disputa de mercados alienígenas, e, consequentemente, melhor posicionar os seus respectivos Estados Nacionais na ordem econômica internacional. Sustenta-se que, hoje, o direito concorrencial pátrio se encontra paralisado pelo discurso liberalizante da globalização; contudo, existem elementos suficientes para uma nova teoria antitruste do dano para tutela da soberania econômica nacional, tendo em vista que o art. 219 da Constituição Federal de 1988 protege o mercado interno como patrimônio nacional, capaz de viabilizar o desenvolvimento cultural e socioeconômico por meio da endogeinização dos centros de decisão nas empresas nacionais. Por fim, defende-se que nova teoria do dano demanda adaptações e flexibilizações às ferramentas tradicionais do direito concorrencial, especialmente em relação à análise: (i) da nacionalidade das pessoas jurídicas envolvidas no ato de concentração; e (ii) das estratégias de financiamento para aquisição da empresa alvo (o abuso de poder econômico- financeiro em atos de concentração); e (iii) do conceito de grupo econômico de empresas estatais. The narrative of globalization is ambiguous, whereby at the international level, the discourse pertains to liberalizing markets so that the most efficient and innovative companies prosper; however, at the domestic level, nations seek to control, meticulously, the entry of foreign capital into their territory. This is particularly evident when considering the merger review with domestic companies, as these economic operations can transfer control of: (i) domestic markets (ii) critical technology and know-how; (iii) strategic infrastructure; and (iv) sensitive information and data. These are elements that individually or together influence the sovereignty of a country. Due to the liberalizing discourse of globalization, it is commonly propagated that antitrust analysis of mergers must be neutral and focused on the trade-off between efficiency and the antitrust damages that could potentially arise. Therefore, this doctoral thesis investigates legal phenomena that deviate from the consensus of orthodox competition law, that is: (i) the incidence of numerous public interests in antitrust legislation; (ii) the instrumentalization of competition law to block undesirable foreign investment in domestic companies and assets; (iii) the effects of state subsidies on private (national champions) and public (state-owned companies) companies to compete for foreign markets, and, consequently, better position their respective nations in the international economic order. It is argued that, today, Brazilian Competition Law is paralyzed by the liberalizing discourse of globalization, however, there are sufficient elements for a new antitrust theory of damage to protect national economic sovereignty, considering that article 219 of the Brazilian Constitution protects the internal market as a national asset, capable of enabling cultural and socioeconomic development through the endogenization of decision-making centers in domestic companies. Finally, it is argued that the new theory of damage demands adaptations to and flexibility of the traditional tools of competition law, especially in relation to the analysis of: (i) the nationality of the companies involved in the merger or acquisition; and (ii) financing strategies involved in mergers and acquisitions (the abuse of economic-financial power); and (iii) the concept of economic group of state-owned companies.
Keywords: Ato de concentração; Foreign direct investment; Fusion acquisition; Fusion-acquisition; Interesse público; Intérêt public; Merger review; National economic security; Public interest; Segurança econômica nacional; Subsidies; Subsídios e investimento direto estrangeiro; Sécurité économique

Desenvolvimento Profissional e Afiliação à Ordem dos Contabilistas na Guiné-Bissau: Motivações e Desafios - Sambú, Luís (Instituto Politécnico de Santarém, 2024)
Objetivo: Esta pesquisa tem como objetivo compreender as motivações que levam os contabilistas acreditados da Guiné-Bissau a se afiliarem à Ordem dos Contabilistas, bem como identificar e compreender as barreiras enfrentadas pelos contabilistas que não são afiliados, com o intuito de propor estratégias que incentivem a afiliação e promovam o desenvolvimento profissional do contabilista no país. Método: Foi utilizada uma abordagem qualitativa. Entrevistas semiestruturadas foram conduzidas com contabilistas acreditados e não acreditados para explorar suas percepções e experiências. A análise de conteúdo foi empregada para interpretar os dados, destacando as motivações para a afiliação e as barreiras enfrentadas pelos não afiliados. Resultado: Os resultados demonstram que os contabilistas acreditados entrevistados não consideram a existência de barreiras. Já os contabilistas não inscritos na ordem mostram-se motivados para se inscreverem na ordem, uma vez que isso lhes permite ter acesso à formação contínua e alcançar estatuto como profissionais de qualidade. Contribuição: A contribuição desta pesquisa consiste em enriquecer o estudo da profissionalização da contabilidade. Igualmente, irá contribuir para uma melhor compreensão do estado da profissão contabilística na Guiné-Bissau. Além disso, dada a inexistência de literatura sobre o tema, este estudo irá ajudar a aumentar o conhecimento das difíceis situações com que os contabilistas acreditados e não acreditados se deparam no exercício das suas funções na Guiné-Bissau.
Keywords: Afiliação; Desafios; Desenvolvimento profissional; Guiné-Bissau; Motivaçoes; Ordem dos contabilistas